Morphology-Controlled Silver-Containing Rhodium Nanoparticles for the Hydrogen Evolution Reaction. Issue 4 (1st April 2022) - Hwang, Gyu Seop; Shin, Woojun; Yim, Gyeonghye; Choi, Jae Hyuk; Kim, Young-Kwan; Jang, Hongje; Kim, Yang-Rae
Abstract : Rh nanoparticles (RhNPs) and Rh-based alloys have attracted significant attention owing to their superior electrocatalytic activity in several energy conversion reactions. Three types of silver-containing RhNPs, namely, nanoshells, nanoframes, and porous nanoplates, have been recently synthesized via inverse directional galvanic replacement. These RhNPs are used in this study to elucidate the relationship between the morphology of RhNPs and their performance in the hydrogen evolution reaction (HER). The activity of RhNPs in HER is investigated using cyclic voltammetry, linear sweep voltammetry, and electrochemical impedance spectroscopy. X-ray photoelectron spectroscopy and X-ray diffraction data reveal that RhNPs contain different Rh/Ag ratios. All RhNPs show long-term stability in acidic conditions. In particular, nanoshells RhNPs exhibit better performance in the low overpotential range than those of Pt/C, a commercial Rh electrocatalyst, and other RhNPs. Thus, the morphology and composition of RhNPs can be controlled for efficient electrocatalysis.